Constructing a holistic approach to disaster risk reduction: the significance of focusing on vulnerability reduction. Issue 1 (January 2014) - Palliyaguru, Roshani; Amaratunga, Dilanthi; Baldry, David
<x xml:space="preserve">Abstract</x> As a result of the increase in natural disaster losses, policy‐makers, practitioners, and members of the research community around the world are seeking effective and efficient means of overcoming or minimising them. Although various theoretical constructs are beneficial to understanding the disaster phenomenon and the means of minimising losses, the disaster risk management process becomes less effective if theory and practice are set apart from one another. Consequently, this paper seeks to establish a relationship between two theoretical constructs, 'disaster risk reduction (DRR)' and 'vulnerability reduction', and to develop a holistic approach to DRR with particular reference to improving its applicability in practical settings. It is based on a literature review and on an overall understanding gained through two case studies of post‐disaster infrastructure reconstruction projects in Sri Lanka and three expert interviews in Sri Lanka and the United Kingdom.